Case Report: A Case of Acute T Lymphoblastic Leukemia With Mixed Infection of Lethal Invasive Mucormycosis and Multi-Drug Resistant Bacteria - Cui, Qingya; Dai, Haiping; Wu, Depei; He, Jun; Xu, Yang; Tang, Xiaowen; Xu, Jie (Frontiers in Medicine, 2022)
Pulmonary mucormycosis (PM) is a rare and life-threatening fungal infection. Here, we report a case of an acute T lymphoblastic leukemia patient with mixed infections of lethal invasive Mucormycosis and multi-drug resistant (MDR) bacteria. After receiving anti-infection drugs to control the patient's fever, he was treated with induction chemotherapy. However, the malignant hematological disease was poorly controlled by the chemotherapy and the patient developed more symptoms of infection. Although the results of multiple β-D-Glucan (G) and Galactomannan (GM) tests remained negative, several pathogens were detected using metagenomic next-generation sequencing (mNGS). In particular, mNGS identified Malassezia pachydermum, Mucor racemosus, and Lauteria mirabilis in the peripheral blood and local secretion samples. The Mucor and bacterial infections were further confirmed via multi-site and repeated fungal and bacterial cultures, respectively. Despite adjusting the anti-infection therapy according to the diagnostic results, the patient's blood disease and symptoms of infection were not alleviated. Additionally, the MDR Acinetobacter baumannii infection/colonization was not confirmed until the seventh culture of the peripheral venous catheter tip. Due to the patient's deteriorating conditions, his family decided to withdraw him from further treatment. Overall, mNGS can facilitate a diagnosis of Mucormycosis by providing clinical and therapeutic information to support conventional diagnostic approaches. For the early and timely diagnosis and treatment of PM, it is also necessary to consider the malignant hematological conditions and repeated tests through multiple detection methods.